Self-nudging Using the Digital Wellbeing App - Krüger, Gustavo; Sachdeva, Nikhil; Sleboda, Patrycja; Zimmermann, Laura; Sobolev, Michael (My University, 2026)
Design of smartphones and their apps can conflict with users’ personal goals and negatively impact well-being, motivating tech companies to develop tools aimed at self-monitoring and altering smartphone usage. This mixed-method study describes the use of self-nudges within Android’s native Digital Wellbeing app as a tool to achieve smartphone usage goals. Students (N = 63) were encouraged to use the Digital Wellbeing app for several weeks, but were given the freedom to select their preferred strategies to curb smartphone usage. Specifically, they could set personal smartphone usage goals and employ features like app ‘Time Limits’, “Grayscale” mode, and “Focus” mode. Results revealed that 58% of participants reported using at least one Digital Wellbeing feature. App time limits were the most utilized, reported by 62.2% of participants, followed by “Do not disturb” mode (43.2%), and “Grayscale” mode (32.4%). Despite this, participants did not rate the Digital Wellbeing app as particularly useful, regardless of whether they used features of the app or not. Participants reported no significant differences in life satisfaction, sleep quality, stress, and happiness before versus after the intervention period. Therefore, self-nudging with the Digital Wellbeing app might not be sufficiently useful and effective due to low engagement and lack of enforcement mechanisms in the app’s tools, which are often bypassed. Based on our findings, we propose implications for future design of digital well being tools, including the integrations of behavioral insights, centering interventions around activity patterns, lowering barriers for uses of those apps, and leveraging machine learning algorithms to adjust intervention strategies over time.
Keywords: 33 Ciencias Tecnológicas; ODS 12 - Producción y consumo responsables; Nudge; Screen Time; Smartphone Overuse; Digital Addiction; Behavior Change